Central Asia: A Comprehensive Crisis and Scenarios for the Future - A. Kazantsev (Международная аналитика, 2015)
The paper suggests a systemic analysis of the perspectives of development of situation in Post-Soviet Central Asia. Interconnection between the tendencies in different spheres (political, economic, military, social and demographic) is analyzed. The author ascertain the fact of complex and multilateral crisis and also states high degree of uncertainty of further development of regional situation, which is indicated by a great variability of scenarios of further development. The analysis is fulfilled both in short- and long-term perspectives. The study is carried out in two steps: for each of temporal perspectives respective drivers that presently exist are selected. Also, potential qualitative discontinuities that can lead to principal changes of situation are defined within scenario analysis.